The Feasibility and Effects of Qigong Intervention (Mind-Body Exercise) in Cancer Patients With Insomnia: A Pilot Qualitative Study. (December 2020) - Low, Sara L. K.; Cheema, Birinder S.; Tan, Hsiewe Ying; Birling, Yoann; Zhu, Xiaoshu
Background: Up to 80% of cancer patients experience insomnia that significantly affects their quality of life. This pilot qualitative study investigated the feasibility and effects of a 3-week Qigong (mind-body exercise) intervention with a 1-week follow-up in cancer patients experiencing insomnia. Methods: Cancer patients with insomnia who had completed radiotherapy or chemotherapy treatment and/or were at least 8 weeks post-cancer-related surgery were recruited. Primary outcomes were feasibility outcomes, which included recruitment, retention, attendance, completion of assessment, adverse events and participant feedback via a questionnaire and focus group/individual interview. Secondary outcomes on insomnia severity and sleep quality were measured using the Insomnia Severity Index (ISI) and the Pittsburgh Sleep Quality Index (PSQI) at baseline, mid, post-intervention and follow-up. Results: Seven participants were recruited and two withdrew from the study. The participant retention rate was 71.4% with an overall attendance rate of more than 84% and participants were able to complete all required assessments. An adverse event relating to the worsening of existing musculoskeletal condition was reported. Qualitative analysis of participant feedback identified 4 emerging themes: (1) experience from Qigong intervention; (2) class preferences; (3) barriers to participation; and (4) recommendation for improvement. Participants reported increased relaxation, improved sleep and energy level, better upper body flexibility and reduced stress. Both ISI and PSQI scores improved significantly ( P < .05). Conclusion: This study demonstrated that it is feasible to employ the current clinical trial design using Qigong intervention on insomnia in cancer patients. Preliminary data suggest that the intervention may improve sleep outcomes, however, these findings need to be confirmed by future robust randomized controlled trials. Trial registration: The trial was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12618001670268)http://www.ANZCTR.org.au/ACTRN12618001670268.aspxon10October2018 .